2022
DOI: 10.1002/mrd.23561
|View full text |Cite
|
Sign up to set email alerts
|

How long can the sperm wait? Effect of incubation time on ICSI outcomes

Abstract: In sperm processing for IVF/ICSI incubation times differ considerably both between and within assisted reproduction facilities. There is no established consensus on the optimal sperm incubation timings to maximize pregnancy rates, and the few studies addressing this association rely on manual and operator-dependent methods for time recording. The present retrospective cohort study includes 1169 ICSI cycles using fresh semen processed by swim-up. An operator-independent, radiofrequency-based system was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, a prospective multicenter cohort study revealed that sperm preparation time in the range of 40–80 min may result in the optimal pregnancy rate [ 152 ]. When it comes to ICSI, several studies observed that no adverse effects were detected on the reproductive outcomes within 5 h [ 9 , 12 , 103 ]. Overall, it suggested that performing IUI or IVF/ICSI immediately after semen collection may be preferable, but the delayed insemination is apparently a feasible alternative for men who are unavailable to provide sperm on the day of oocyte retrieval [ 37 ].…”
Section: Effects Of Extended Non-freezing Storage Of Human Spermatozo...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a prospective multicenter cohort study revealed that sperm preparation time in the range of 40–80 min may result in the optimal pregnancy rate [ 152 ]. When it comes to ICSI, several studies observed that no adverse effects were detected on the reproductive outcomes within 5 h [ 9 , 12 , 103 ]. Overall, it suggested that performing IUI or IVF/ICSI immediately after semen collection may be preferable, but the delayed insemination is apparently a feasible alternative for men who are unavailable to provide sperm on the day of oocyte retrieval [ 37 ].…”
Section: Effects Of Extended Non-freezing Storage Of Human Spermatozo...mentioning
confidence: 99%
“…Some studies proposed that hypothermic preservation can be a substitute for cryopreservation if spermatozoa could be obtained surrounding the day of ART [ 10 , 11 ]. Besides, sperm acquired for ART undergo a prolonged incubation in artificial gamete or embryo cultural media, which may compromise its fertility [ 12 , 13 ]. Optimization of the sperm’s functional competence during this period is supposed to improve the clinical outcome of ART [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%